Hubungan Pengetahuan Remaja dengan Perilaku Seksual Pra Nikah pada Siswa Kelas Xl di SMK Kesehatan Plus Prima Mandiri Sejahtera Makassar - Muldaniyah, M (Utan Kayu Publishing, 2021)
Sexual behavior is understood as a from of behavior that arise because of their sexual drive or youth activities to get the pleasure of sexual organs through a variety of manners. This study aims to determine the factor-factor that influence sexual behavior before marriage in health SMK Kesehatan Plus Prima Mandiri Sejahtera Makassar in 2016. This study uses the cross-sectional method. Samples were taken as many as 50 respondents graders XI Health Plus Prima Mandiri Sejahtera Makassar who meet the inclusion criteria. How sampling using purposive sampling techniques, With Univariate Data Analysis and Data Bivariate. The research was conducted in May 2016 using a questionnaire. The data is processed and analyzed using SPSS statistical approach 16. The results of this study show that the knowledge of p = 0,019 (p less than 0,05), the behavior of p =0,019 (p = less than 0,05). It can be concluded that there is a relationship between knowledge with premarital sexual behavior. Suggestions in this study are expected to be a reference point for students about the effects of premarital sex, look for a good source of information and be accurate.